Pengembangan Lembar Kerja Peserta Didik (LKPD) Terintegrasi Al-Qur’an dan Hadits pada Materi Sistem Pertahanan Tubuh - Putri Arya Salsabila; Ratu Permatasari; Fuji Barlian Andini; Ummi Hiras Habisukan; Amin Nurokhman (Jurnal Inovasi Pembelajaran Biologi, 2026)
This study aims to develop and evaluate the feasibility of an Integrated Al-Qur’an and Hadith Student Worksheet (LKPD) on the topic of the Body’s Defense System for high school students. The study employed the Research and Development (R&D) method using the ADDIE model, limited to the development phase. The instruments used include validation questionnaires by subject matter experts, language experts, media experts, and religious experts, as well as student and teacher response questionnaires. Quantitative data were analyzed using percentage techniques, while qualitative data were analyzed through the reduction and interpretation of comments. Validation results showed that the worksheets received 97.33% from religious experts, 96.00% from subject matter experts, 97.33% from media experts, and 96.00% from language experts, all categorized as highly valid. A limited pilot test indicated that students rated the worksheets at 90.96% (very practical), while teachers rated them at 89.33% (practical). Student comments indicated that the worksheets were engaging, easy to understand, and helped connect biological concepts with Islamic values. Based on these findings, the worksheets were deemed suitable for use as printed instructional materials and have the potential to be implemented in high school biology instruction.